Experimental evidence on post-program effects and spillovers from an agriculture-nutrition program - Dillon, Andrew; Bliznashka, Lilia; Olney, Deanna K. (Elsevier, 2020)
Integrated agricultural-nutrition programs are often implemented under the premise that program effects are durable and spillover. This paper estimates one year post-program effects, three-year aggregate program effects and spillover effects using treated and untreated household cohorts. Two treatment interventions implemented agricultural interventions with behavior change communication strategies varying implementers using either village health committees or older female leaders. In the post-program period, program effects deteriorated relative to program period impacts documented in Olney et al. (2015), but the three-year agricultural, nutrition knowledge, health care practices and severe anemia impacts remained statistically significant. Despite the non-rival nature of nutrition education and promoted production techniques, there is little evidence of agricultural technology or health knowledge spillovers to non-treated households within treatment communities. Spillover effects measured for appropriate treatment of diarrhea (10 pp increase in giving rehydration salts rather than traditional medicine), wasting (20 pp lower probability of wasting) and children’s anemia status (7 pp reduction in severe anemia) significantly improve in later cohorts. The aggregate program effects and spillovers are generally robust to multiple hypothesis testing.